Performance of Prilled Urea and Urea Super Granule by Applicators on Yield and Nitrogen Use Efficiency in Boro Rice - Hossain, ATMS; Rahman, F; Saha, PK (Bangladesh Rice Journal, 2019)
A field experiment was conducted on validation of prilled urea (PU) and urea super granule (USG) applied by applicators on yield and nitrogen use efficiency during Boro 2014 season at Bangladesh Rice Research Institute (BRRI) farm, Gazipur (AEZ 28). Six treatment combinations of different N doses and methods of N application were tested to compare urea-N application by PU and USG applicator for rice yield, N uptake and N use efficiency over urea broadcasting. Application of N as PU or USG through applicator has same effect on grain yield, N uptake and N use efficiency compared with urea broadcasting. Statistically similar grain yield were observed with N application as PU or USG @ 78 kg N ha-1 by applicator which was comparable with urea broadcasting @ 135 kg N ha-1. The N concentration and uptake in both panicle initiation (PI) and maturity stage were higher in USG deep placement than PU deep placement by applicators but the difference was not significant. Although agronomic use efficiency (AUE) of N was slightly higher in PU than USG applied by applicators but the recovery efficiency (RE) of N was higher in USG than PU. Bangladesh Rice j. 2018, 22(2): 63-69